2020
DOI: 10.3389/fnins.2020.00901
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Alterations of Amplitude of Low-Frequency Fluctuations in Patients With Drug-Naïve First-Episode Early Onset Schizophrenia

Abstract: Abnormalities in static neural activity have been widely reported in early onset schizophrenia (EOS). However, dynamic brain activity alterations over time in EOS are unclear. Here, we investigated whether temporal dynamic changes in spontaneous neural activity are influenced by EOS. A total of 78 drug-naïve first-episode patients with EOS and 90 healthy controls (HCs) were enrolled in this study. Dynamic amplitude of low-frequency fluctuations (dALFF) was performed to examine the abnormal time-varying local n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…The ALFF method has been applied to evaluate the neural mechanisms of central disease including schizophrenia ( 21 ), epilepsy ( 22 ), mild cognitive impairment ( 23 ), and migraine ( 24 ). Besides, many studies have suggested that the ALFF of fMRI signals are closely related to the spontaneous neuronal activities such as visual cortex ( 25 ), auditory cortex ( 26 ), hippocampus ( 27 ), cingulate cortex, and postcentral gyrus ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ALFF method has been applied to evaluate the neural mechanisms of central disease including schizophrenia ( 21 ), epilepsy ( 22 ), mild cognitive impairment ( 23 ), and migraine ( 24 ). Besides, many studies have suggested that the ALFF of fMRI signals are closely related to the spontaneous neuronal activities such as visual cortex ( 25 ), auditory cortex ( 26 ), hippocampus ( 27 ), cingulate cortex, and postcentral gyrus ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oscillatory signaling is ubiquitous in vital movement, and precisely controls the sequential behaviors of many important physiological processes [1][2][3], such as circadian rhythm [4], embryonic development [5], neuron electrophysiology [6], and cell cycle [7]. Oscillation behavior of molecules, for instance, calcium ions, tumor suppressor gene p53, p38 MAPK (mitogenactivated protein kinases), and NF-κB (Nuclear Factor-kappa B) in inflammatory response, determines the fate of cells [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used VBM and ALFF methods to investigate changes in GMV and local neural activity in patients with schizophrenia ( 44 48 ). The TP, MFG, and MTG are the common brain areas consistently reported in previous studies and the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, compared with healthy participants, some studies found that patients with schizophrenia demonstrate decreased GMV in the MFG and paralimbic system (including the orbitofrontal cortex, insular cortex, and TP) ( 44 , 45 ). Li et al found differences in the variability of dynamic ALFF between EOS patients and healthy controls in the bilateral precuneus, right superior marginal gyrus, right postcentral gyrus, and right MTG ( 48 ). However, the investigators focused solely on distinguishing this disease and paid no attention to changes in the global cognitive function of patients.…”
Section: Discussionmentioning
confidence: 99%